Effect of platelet-rich plasma on bone healing of autogenous bone grafts in critical-size defects - Nagata, Maria José Hitomi [UNESP]; Melo, Luiz. G. N. [UNESP]; Messora, Michel R. [UNESP]; Bomfim, Suely Regina Mogami [UNESP]; Fucini, Stephen E. [UNESP]; Garcia, Valdir Gouveia [UNESP]; Bosco, Álvaro Francisco [UNESP]; Okamoto, Tetuo [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
AimThis study histologically analysed the effect of autogenous platelet-rich plasma (PRP), prepared according to a new semiautomatic system, on healing of autogenous bone (AB) grafts placed in surgically created critical-size defects (CSD) in rabbit calvaria.Material and MethodsSixty rabbits were divided into three groups: C, AB and AB/PRP. A CSD was created in the calvarium of each animal. In Group C (control), the defect was filled by blood clot only. In Group AB (autogenous bone graft), the defect was filled with particulate autogenous bone. In Group AB/PRP (autogenous bone graft with platelet-rich plasma), it was filled with particulate autogenous bone combined with PRP. All groups were divided into subgroups (n=10) and euthanized at 4 or 12 weeks post-operatively. Histometric and histologic analyses were performed. Data were statistically analysed (anova, t-test, p < 0.05).ResultsGroup C presented significantly less bone formation compared with Group AB and AB/PRP in both periods of analysis (p < 0.001). At 4 weeks, Group AB/PRP showed a statistically greater amount of bone formation than Group AB (64.44 +/- 15.0% versus 46.88 +/- 14.15%; p=0.0181). At 12 weeks, no statistically significant differences were observed between Groups AB and AB/PRP (75.0 +/- 8.11% versus 77.90 +/- 8.13%; p > 0.05). It is notable that the amount of new bone formation in Group AB/PRP at 4 weeks was similar to that of Group AB at 12 weeks (p > 0.05).ConclusionWithin its limitation, the present study has indicated that (i) AB and AB/PRP significantly improved bone formation and (ii) a beneficial effect of PRP was limited to an initial healing period of 4 weeks.
Keywords: bone grafting; bone regeneration; growth factors; in vivo model; platelets